PENTINGNYA PENDIDIKAN KEWARGANEGARAAN DALAM MEMINIMALISIR PENGARUH GLOBALISASI TERHADAP KARAKTER CINTA TANAH AIR PADA SISWA SMAN 1 MAJALAYA - Riski Fauzi Amelia; Dinie Anggraeni Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The influx of globalization has influenced many aspects of life on earth, especially for our country, Indonesia. This study aims to determine how much influence the globalization of Citizenship Education has on the character of love for the country among students of SMAN 1 Majalaya. The research method used is descriptive qualitative with interview techniques through online media g-form. The results of the study show that Citizenship Education has a great influence in instilling a love of the country character and minimizing the influence of globalization on students of SMAN 1 Majalaya.